Executive Summary of the Economic Contributions and Ecosystem Services of Springs in the Lower Suwannee and Santa Fe River Basins of North-Central Florida - Tatiana Borisova; Alan W. Hodges; Thomas J. Stevens (EDIS)
This study examined the economic contributions, consumer surplus, and ecosystem services provided by recreational use of fifteen major springs sites in north central Florida. The estimated annual economic contributions of springs-related recreational spending in north-central Florida for FY 2012/13 are summarized. Among the findings, there was $84.2 million in total visitor spending for springs recreation, and 1,160 full- and part-time jobs. This 4-page fact sheet was written by Tatiana Borisova, Alan W. Hodges, and Thomas J. Stevens, and published by the UF Department of Food and Resource Economics, April 2015.